Patterns of ecstasy use amongst live music event attendees and their opinions on pill testing: a cross sectional study - Madeleine Southey; Ashwini Kathirgamalingam; Benjamin Crawford; Rohan Kaul; Jack McNamara; Franklin John-Leader; Jenny Heslop; Sabrina Winona Pit (Substance Abuse Treatment, Prevention, and Policy, 2020)
Abstract Background Pill testing services could potentially be used to reduce drug-related harm. This study aims to identify patterns of ecstasy use among live music event attendees; explore the opinions and potential usage of illicit pill testing programs and examine factors associated with the likelihood of still taking a pill containing a potential harmful substance. Methods A cross-sectional survey was completed by 760 people attending a major Australian live music event in 2017. Results The most commonly used drug in the last 12 months was ecstasy (73.9%). About 5% of people who use drugs had sought medical attention due to consumption of ecstasy. People who use drugs agreed “a lot” that pill testing should be provided for free at live music events (82.2%) and that it should be combined with harm reduction advice (62.9%). Additionally, 32% of all participants agreed ‘a lot’ that they would be more likely to take illicit drugs at a music festival if pill-testing services were present. However, if people perceived that a harmful substance was detected in their drugs after using a pill testing service, 52.3% of people who have used illicit drugs reported that they would ‘not at all’ be likely to still consume the drug. They also reported that they would still take a pill if testing demonstrated the presence of unintended MDMA-type substances (70.3%), amphetamines (31.2%) or ketamine (27.8%). Multivariate analyses demonstrated that only increased frequency of ecstasy use was significantly associated with taking a pill despite pill testing services detecting a harmful substance. Gender, age, alcohol and previously seeking ecstasy-related medical attention were not associated in the multivariate analyses. Conclusions A high proportion of live music attendees consume alcohol and ecstasy. Both people who have and who have not used illicit drugs support the implementation of pill testing services. People reported they would change their consumption patterns according to the results given by pill testing services. The findings may be used to stimulate public debate, and assist drug and alcohol policy makers in the implementation of harm minimisation strategies such as combining pill testing services with harm reduction advice.